Proposed new interior design of wedding boutique at 118, Lorong Maarof, Taman Bangsar, 59100, Kuala Lumpur for Salikin Sidek Sdn. Bhd / Puteri Nur Balqis Jaffry - Jaffry, Puteri Nur Balqis (Faculty of Architecture, Planning and Surveying, 2012)
The project is proposing a new wedding boutique for the client, Salikin Sidek Sdn Bhd. Salikin Sidek wanted to open a new wedding boutique for his bridal collection. The site is located in 118, Lorong Maarof, Taman Bangsar, 59100, Kuala Lumpur. Aim of the project is to design a wedding boutique with new ambience as required by the client and more space and display area. The concept applied into the boutique is ‘Sekapur Sireh, Seulas Pinang’. The concept is combination of two style. Which is modern and malay traditional. The material used is more to modern material such as metal, glass, plastics but most of the furniture applied is classical concept. The colour scheme used is black, white, grey and a little touch of golden brown.